Corporate Political Strategies and Return Predictability. Issue 4 (1st September 2018) - Kim, Chansog (Francis); Kim, Incheol; Pantzalis, Christos; Park, Jung Chul
Abstract : We assess whether observable corporate political strategies can serve as channels of value-relevant political information flow into stock prices and form the basis for profitable return predictability strategies. We document that returns of politically connected firms' stocks lead those of their non-connected peers, suggesting that information shocks associated with new policies and other political developments become evident first in the stock prices of firms that pursue political strategies and then, with delay, in those of similar, non-connected firms. Abstract : It's often said that money and power go hand in hand. Now there is hard evidence that investors can achieve outperformance by analyzing the political connectedness of companies. Abstract : A practitioner's perspective on this article is provided in the In Practice piece "The Predictive Power of Politics " by Phil Davis. Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 29 September 2017 Accepted 23 July 2018 by Stephen J. Brown This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in the acknowledgments. Heiko Bailer and Claude B. Erb, CFA, were the reviewers for this article.